1987
DOI: 10.1002/pssb.2221400207
|View full text |Cite
|
Sign up to set email alerts
|

Localized vibrations of hydrogen and deuterium in GaAs. A comparison with Ge and Si

Abstract: A detailed study is made of the localized vibrational stretching modes of hydrogen in GaAs using high-energy proton implantation and low-temperature Fourier transform infrared spectroscopy. New mode frequencies are found and confirmed with the help of deuterium implantation. A comparison with proton-and deuteron-implanted germanium shows a different shape of the vibrational bands in comparison to GaAs. The oscillator strengths and effective charges are determined for the vibrational bands observed.Mittels Hoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 14 publications
(7 reference statements)
1
5
0
Order By: Relevance
“…Infrared absorption spectrum measurements have been successfully employed as a method for the investigation of the localized vibrational modes (LVMs) in semiconductors. There have been a few studies of the hydrogen-induced LVMs in proton-implanted gallium arsenide [2,3]. The results were confirmed with the help of deuterium implantation in the same GaAs samples which had been hydrogen implanted.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Infrared absorption spectrum measurements have been successfully employed as a method for the investigation of the localized vibrational modes (LVMs) in semiconductors. There have been a few studies of the hydrogen-induced LVMs in proton-implanted gallium arsenide [2,3]. The results were confirmed with the help of deuterium implantation in the same GaAs samples which had been hydrogen implanted.…”
Section: Introductionsupporting
confidence: 73%
“…The implantation dose for each energy was 2 x 1015 ions/cm2, so the total dose is 1 x 1OI6 ionsJcm2. This is about the same as that used in [2] and about two order of magnitude lower than that used in [3]. Infrared absorption measurements in the range between 4000 and 400cm-' have been performed with a Bruker IFS 113V Fourier transform spectrometer at an instrumental resolution of 0.2 or 0.5 cm-' for samples investigated in the temperature range of 4.2 to 225 K (using a refrigerator cryostat of Air Product) and a resolution of 2 cm-' for the samples at room temperature,' 295 K. (where 01 is the absorption coefficient as a function of frequency v), the linewidth (the full width at half maximum), and the frequency of the absorption peak as functions of temperature.…”
Section: Methodsmentioning
confidence: 83%
“…2,[6][7][8] The 2029 cm Ϫ1 in hydrogen-implanted GaAs has been assigned to a stretch mode for As-H bonds. 15 Assignments for the Ga-H and As-H bands are firmly based upon frequency shifts produced by hydrogen isotope substitution, upon substitution of the group III and group V constituents ͑e.g., InAs and InP substituted for the GaAs host 15 ͒, and upon correspondence of the observed frequencies to those for Ga-H and As-H bonds in solids.…”
Section: Resultsmentioning
confidence: 99%
“…In Si, for example, the annealing characteristics for an Si-H center produced by hydrogen implantation near 100 K were shown to correlate 21 with those for vacancies identified and characterized in EPR studies. 22 Previous studies on GaAs following hydrogen implantation at room temperature [6][7][8] have shown that annealing of Ga-H centers correlates with annealing of vacancy-interstitial pairs (V As -As i ) or V As defects produced on the As sublattice. The As sublattice defect assignments were made in deep-level transient spectroscopy ͑DLTS͒ studies, 23 and the Ga-H centers observed in infrared absorption studies have been attributed to hydrogen bonded to Ga atom neighbors of displaced As atoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation